Strategic management of the home care program the Makassar City Government, Indonesia - Kurupunda, Muhaimin L. Hi.; Yunus, Muhammad; Abdullah, Muh. Tang; Pratama, Muhammad Fathurahman (Institute of Computer Science (IOCS), 2025)
This study aims to identify the stages in strategic management that pose challenges, resulting in the suboptimal implementation of the home care program. The research employs a descriptive qualitative approach to comprehensively understand the objectives. The findings indicate that to enhance the quality of healthcare services in Makassar City, the Makassar City Government introduced the home care program through Makassar Mayor Regulation No. 6 of 2016 on 24-hour home care services. The main obstacle in implementing the program is the limitation of access to home care services for certain segments of the community. The implication of this study is the need for strategic evaluations to address the limitations in the utilization of home care services by the public. Without such evaluations, the program will not operate effectively.